ANALISIS KEBERHASILAN SISTEM INFORMASI DALAM MENDUKUNG IMPLEMENTASI E-GOVERNMENT: STUDI PADA DENPASAR INTEGRATED VIRTUAL OFFICE SYSTEM - Aris Veratiani, Gek (Penerbit Lafadz Jaya, 2025)
Changes in people’s work patterns after the COVID-19 Pandemic have created demands for the community to be able to adapt to changes in work patterns, especially in the use of appropriate information technology. The purpose of this study was to analyze the success of the Denpasar Integrated Virtual Office System (DIVOS) in implementing e-government in Denpasar City. This study was designed using a qualitative approach and descriptive analysis methods, presenting information system success theories and interpreting them through supporting data from the DIVOS implementation process during work-from-home periods. The results of this study indicate that DIVOS has achieved its goal of assisting civil servants (ASN) while working from home. In addition to the quality of the information system, DIVOS's success is also supported by a work culture and digital performance management built through the Performance Chain feature, which includes reporting and performance evaluation. However, continuous improvements are still needed. Several indicators of information system quality need to be improved, including the quality of the system's integration with Denpasar's official website, the provision of DIVOS user complaint services, and the usability of the system according to user needs.